Enhancement Of Bacterial Iron And Sulfate Respiration For In-Situ Bioremediation Of Acid Mine Drainage Sites: A Case Study - A. Azra Bilgin; James M. Harrington; JoAnn Silverstein (Society for Mining, Metallurgy & Exploration, 2005)
The prevention of AMD in situ is more attractive compared to subsequent downgradient treatment alternatives that do not involve source control. AMD source control can be achieved by shifting the microbial activity in the sulfidic rock from pyrite oxidation to anaerobic heterotrophic activity. This is achieved by adding biodegradable organic carbon amendments to the sulfidic rock. This technique was applied in an abandoned mine pool with a pH of 3-3.5. Following treatment, near-neutral pH and decreased effluent heavy metal concentrations were achieved. In situ bioremediation by enhancement of bacterial iron and sulfate reduction is a promising technology for AMD prevention.